THE PHYSICAL PROCESSES AT SUPERCONDUCTIVITY IN PAIRS OF FRICTION BRAKES - Kindrachuk, Myroslav; Volchenko, Dmytro; Skrypnyk, Vasyl; Prisyazhniy, Andrii; Nishchuk, Viktor (Problems of Friction and Wear, 2023)
The theoretical and experimental studies of the main physical parameters in the case of superconductivity of a metallic friction element, which is under the unilateral action of thermal, electric and magnetic fields, made it possible to establish the following. The energy of an electron in a crystal lattice cannot take on any values due to the fact that there are sets of discrete energy levels (zones) separated by more or less significant distances. Heat capacity and thermal conductivity have components that relate to electrons and the crystal lattice; the heat capacity in the state of superconductivity turned out to be less than the heat capacity of a normal metal, and the heat conductivity increased due to the local interaction of microprotrusions of friction pairs. In the surface layer of the metal under the action of a magnetic field, a stationary electric current arises, which has its own magnetic field opposite to the applied field, which, as a result, leads to a zero value of induction in the surface layer of the metal. At a critical value of the magnetic field strength, the subsurface layer of the metal friction element goes into a normal state.